Analisis Tingkah Laku Manusia pada Naskah Pastur Cethil (Kajian Filologi) - Adelia, Dea Adies; Venny Indria; Wulan, Sri Hertanti; Restu Budiyanti; Fitri Rokhimah (Kawruh: Journal of Language Education, Literature and Local Culture, 2024)
Behavior is an action or behavior of a person in living life. Human behavior can be researched through ancient Javanese texts. This research aims to present Pastor Cethil's text in accordance with philological studies and explain human behavior in Pastor Cethil's text. The object of research is the text in Pastor Cethil's manuscript which is written using Javanese script in the Javanese language krama. The data collection technique in this research uses several steps consisting of; inventory of the Pastor Cethil manuscript, description of the Pastor Cethil manuscript, transliteration of the Pastor Cethil manuscript text, editing of the Pastor Cethil manuscript text, translation of the Pastor Cethil manuscript text, and analysis of human behavior in the Pastor Cethil manuscript. This research is a type of descriptive qualitative research that uses modern philological methods and descriptive methods with a behavioral psychology approach. Data analysis techniques include data reduction, data classification, data presentation, and data verification. The results of research on the behavior of each character in Pastor Cethil's text show several good and bad behaviors towards God, fellow humans and himself. Good behavior towards God is like obeying religious regulations as a priest who is not allowed to marry. Bad behavior towards others, one of which is inappropriate indulgence in lust with the opposite sex, can cause disaster in the future. Some of the human behavior in Pastor Cethil's text can be a picture of life that should be imitated or should be avoided.